4CPS-216 Prescription of fall-risk-increasing drugs in patients suffering a fall with major lesions during admission at an intermediate care centre. (March 2019) - De Andrés, AM; Romano, E; García-Salmones, M; Pérez, LM; Inzitari, M
Abstract : Background: Falls in the elderly increase morbidity, affect quality of life and increase healthcare costs. Several pharmacological groups have been associated with falls, which are grouped as 'Fall Risk Increasing Drugs' (FRIDs). Despite awareness of the risk, the prescription of FRIDs is highly prevalent. Purpose: To assess prescription patterns in patients experiencing a fall which resulted in major lesions during admission at an intermediate care centre. To determine the prevalence of FRIDs before and after the fall. Material and methods: Observational and retrospective study of patients admitted to an intermediate care centre of 350 beds in an urban area, who experienced a major lesion (reported below) due to a fall during a 3 year period (2015–2017). They were identified by the inpatient fall register. Data regarding treatment was collected from the digital health record. The main outcome was the prescription of FRIDs. The following variables were collected: demographics (age, sex), type of lesion, and number and type of drugs (ATC codes) prior to fall and at discharge. The FRIDs list was built from a literature review and included: cardiovascular drugs (CV); psychotropic; and others (NSAIDS, opioids, anti-epileptics). Statistical analysis was performed with Stata v15. Results: We included 50 patients (mean age ±SD=79.3±11.4, 54% males). The consequences of the fall were: traumatic brain injury (n=11), wound requiring stitches (n=15), fracture (n=17) and others (n=7). Prior to the fall, the average number of total drugs/patient was 11.1±3.2: 96% received at least one FRID (42% ≥4 FRIDs, 3.4±1.8 FRIDs/patient). One-hundred and seventy-one prescriptions of FRIDs were identified: 44.4% CV drugs, 40.35% psychotropic drugs and 15.2% others. Eighty per cent of patients received a psychotropic drug (mainly benzodiazepines or quetiapine) prior to the fall. Twenty-eight patients were discharged home or to a long-term care facility (n=5 exitus, n=17 acute care). Of these, 92.9% received a FRID prior to discharge (50%≥4 FRIDs, 3.6±2.1 FRIDs/patient). Only in eight patients (28.6%) were some FRIDs discontinued (10 FRIDs). Conversely, 11 new FRIDs were initiated in eight patients. Conclusion: Despite being a well-known modifiable risk factor for falls, the prescription of FRIDs is highly prevalent among the elderly. In our sample, the withdrawal of FRIDs appears not to be a usual practice, even after a relevant adverse event. References and/or acknowledgements: No conflict of interest.